2016
DOI: 10.1051/bioconf/20160702024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sequential inoculation (Torulaspora delbrueckii/Saccharomyces cerevisiae) in the first fermentation on the foam properties of sparkling wine (Cava)

Abstract: Abstract. In a previous study we reported that sequential inoculation of Torulaspora delbrueckii and Saccharomyces cerevisiae during the first fermentation increased the protein concentration and improved the foaming properties of a base wine. Since effervescence and foam of sparkling wines are key quality factors, the interest of this practice for sparkling wine industry is obvious. In this paper we study whether the foaming properties of the sparkling wines produced from the base wines obtained by sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In reference to esters, it has been demonstrated that their production is closely related to the amount of yeast assimilated nitrogen (YAN) available in the must but, depending on the yeast characteristics, their production might increase or decrease with increased levels of YAN ( Carrau et al, 2008 ). The levels of ethyl acetate, with pleasant fruity aromas when the concentration is under 60 mg/L ( Medina-Trujillo et al, 2016 ) or varnish aromas when the concentration is higher, were similar to those observed in other recently published articles in which Lt was also used, with an ethyl acetate production of about 15–25 mg/L ( Canonico et al, 2019 ; Vaquero et al, 2020 ). In contrast, higher concentrations have also been obtained in previous works ( Morata et al, 2019b ; Vaquero et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In reference to esters, it has been demonstrated that their production is closely related to the amount of yeast assimilated nitrogen (YAN) available in the must but, depending on the yeast characteristics, their production might increase or decrease with increased levels of YAN ( Carrau et al, 2008 ). The levels of ethyl acetate, with pleasant fruity aromas when the concentration is under 60 mg/L ( Medina-Trujillo et al, 2016 ) or varnish aromas when the concentration is higher, were similar to those observed in other recently published articles in which Lt was also used, with an ethyl acetate production of about 15–25 mg/L ( Canonico et al, 2019 ; Vaquero et al, 2020 ). In contrast, higher concentrations have also been obtained in previous works ( Morata et al, 2019b ; Vaquero et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…Hanseniaspora vineae has a medium fermentative power (9–10% v/v; Martin et al, 2018 ) and medium adaptation to the increase of ethanol ( Díaz-Montaño and de Jesús Ramírez Córdova, 2009 ), but a high contribution at the sensory level since it produces a large amount of aromatic compounds ( Medina et al, 2013 ), such as 2-phenylethyl acetate and benzenoids, when used in monocultures or sequentially ( Medina et al, 2013 ; Lleixà et al, 2016 ). Torulaspora delbrueckii is also widely used at an industrial level due to its low volatile acidity and contribution to wine fruitiness, structure ( Jolly et al, 2013 ), and improvement in the texture of the wine ( González-Royo et al, 2014 ; Medina-Trujillo et al, 2016 ). Metschnikowia pulcherrima has a low fermentative power ( González et al, 2018 ); however, it produces a large quantity of terpenes, thiols, and esters, such as ethyl octanoate associated with the pear aroma ( Clemente-Jimenez et al, 2004 ; Sadoudi et al, 2012 ), reduces the alcohol content ( Contreras et al, 2014 ; Ciani et al, 2016 ), and can produce significant amounts of 2,6-dimethoxyphenol with a smoky aroma ( Culleré et al, 2004 ; González-Royo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively limited research has evaluated the application of non-Saccharomyces yeast in sparkling wine production than still wines. Existing studies on non-Saccharomyces yeast for traditional method sparkling wine production have evaluated T. delbrueckii, M. pulcherrima, S. pombe and Saccharomycodes ludwigii as either solitary fermenters or in co-inoculation with S. cerevisiae (González-Royo et al, 2015;Medina-Trujillo et al, 2016;Canonico et al, 2018;Tofalo et al, 2022). In sparkling wines, non-Saccharomyces yeast strains may be useful for metabolite production and amino acid composition, although concerns surrounding the use of these strains for second alcoholic fermentation have been raised, particularly due to the production of select metabolites which can negatively influence sensory attributes Ivit and Kemp, 2018;Cotea et al, 2021).…”
Section: Non-saccharomyces Yeastmentioning
confidence: 99%
“…They found that the sparkling wine obtained using Metschnikowia pulcherrima had a longer persistence of the foam and an interesting aromatic profile, with notes of smoke and flowers. Reports show that Torulaspora delbrueckii decreases volatile acidity but increases the proportion of glycerol, thus improving the foaming properties of wine due to the autolysis of yeasts [45]. Sparkling wines produced with Saccharomycodes ludwigii and Schizosaccharomyces pombe display important changes in color characteristics, acidity, volatile profile, and biogenic amines [31].…”
Section: Yeast Selection In the Technology Of Sparkling Wine Productionmentioning
confidence: 99%